Mapping warming reefs—An application of multibeam acoustic water column analysis to define threatened abalone habitat - Lucieer, Vanessa; Flukes, Emma; Keane, John P.; Ling, Scott D.; Nau, Amy W.; Shelamoff, Victor (Frontiers in Remote Sensing, 2023)
Robust definition of the spatial extent of habitats and how they may be changing through time is a holy grail for ecosystem management, particularly if an ecosystem is approaching a tipping point beyond which irreversible changes may occur. Here we generate and explore a new data set for the management of warming reefs in eastern Tasmania that will significantly improve the baseline maps required for fine-scaled spatial modelling and management that is both robust at regional scales but is highly resolved within the water column. This process enabled the relative density of kelp vegetation to be identified in a region that is being overwhelmed by the range extension of a destructive grazer, the Longspined Sea Urchin Centrostephanus rodgersii. We present a new online tool to visualize water column acoustic data as surfaces of kelp density over high resolution (50 cm) scale seafloor terrain maps (spanning a total straight-line distance of 594 km and a total area of 29.14 km2) to reveal the types of reef structure on the East Coast of Tasmania where abalone habitat is threatened by kelp loss.